The shifting scales of justice : the Supreme Court in neo-liberal India - Suresh, Mayur; Narrain, Siddharth (New Delhi : Orient Blackswan, 2014)
Papers presented at the conference on the "Judicial Nineties" held i n Bangalore in 2008.
Includes bibliographical references and index.
Keywords: India. -- Supreme Court -- Congresses; Judicial power -- India -- Congresses; Public interest law -- India -- Congresses; Citizen suits (Civil procedure) -- India -- Congresses